Kontribusi Manajemen Waktu dan Beban Kerja terhadap Prestasi Akademik Mahasiswa Pekerja Paruh Waktu - Rosita Rosita; Tarishah Cathabella; Munparidi Munparidi; Sari Lestari Zainal Ridho; Dwi Riana (Jurnal Simki Economic, 2026)
This study aims to analyze the influence of Time Management (X1) and Workload (X2) on Academic Achievement (Y) in part-time working students. The study used a quantitative approach with multiple linear regression methods and a Likert scale instrument of 1–5. Respondents were 100 part-time working students from various study programs. The results of the study indicate that the Time Management variable (X1) has a positive and significant effect on Academic Achievement (Y). In addition, Workload (X2) is also proven to have a positive and significant effect on students' Academic Achievement. A measurable workload can improve discipline, the ability to organize tasks, and motivation in completing academic responsibilities. Simultaneously, both variables, namely Time Management and Workload, have a significant effect on Academic Achievement. Based on these findings, it is recommended that students improve their time management skills by preparing a balanced study and work schedule.